Risk factors and prevention of cardiovascular complications in breast cancer - M. N. Mamedov; A. K. Karimov; E. K. Saribekyan; A. D. Zikiryakhodjaev (Кардиоваскулярная терапия и профилактика, 2025)
Breast cancer (BC) is the most common malignant tumor in women. In patients who have undergone antitumor treatment at an early stage of BC, death in the long term more often occurs from cardiovascular diseases (CVD) than from cancer. Numerous studies indicate that the risk of cardiomyopathy and/or heart failure, coronary artery disease among BC survivors who received anthracyclines and/or trastuzumab is increased. Currently, early detection of cardiotoxicity using cardiac imaging and circulating cardiovascular biomarkers is widely evaluated in clinical trials. At the same time, the high risk of CVDs observed in cured breast cancer survivors is a consequence of both the adverse effects of anticancer therapy on the cardiovascular system, including antiestrogens, and the presence of common cancer and CVD risk factors. Large clinical trials reported higher rates of hypertension, hypercholesterolemia, and ischemic CVD in postmenopausal BC survivors receiving aromatase inhibitors. Strategies for the prevention and treatment of left ventricular dysfunction or heart failure in such patients should include a comprehensive cardiovascular risk evaluation and individual clinical assessment.